Intracellular delivery of cell-penetrating peptide-transcriptional factor fusion protein and its role in selective osteogenesis - Suh JS (Dove Medical Press, 2014)
Jin Sook Suh,1,* Jue Yeon Lee,2,* Yoon Jung Choi,1 Hyung Keun You,3 Seong-Doo Hong,4 Chong Pyoung Chung,2 Yoon Jeong Park1,2 1Dental Regenerative Biotechnology, Dental Research Institute, School of Dentistry, Seoul National University, Seoul, 2Central Research Institute, Nano Intelligent Biomedical Engineering Corporation (NIBEC), Seoul, 3Department of Periodontology, College of Dentistry, Wonkwang University, Iksan, 4Department of Oral Pathology, School of Dentistry, Seoul National University, Seoul, Republic of Korea *These authors contributed equally to this work Abstract: Protein-transduction technology has been attempted to deliver macromolecular materials, including protein, nucleic acids, and polymeric drugs, for either diagnosis or therapeutic purposes. Herein, fusion protein composed of an arginine-rich cell-penetrating peptide, termed low-molecular-weight protamine (LMWP), and a transcriptional coactivator with a PDZ-binding motif (TAZ) protein was prepared and applied in combination with biomaterials to increase bone-forming capacity. TAZ has been recently identified as a specific osteogenic stimulating transcriptional coactivator in human mesenchymal stem cell (hMSC) differentiation, while simultaneously blocking adipogenic differentiation. However, TAZ by itself cannot penetrate the cells, and thus needs a transfection tool for translocalization. The LMWP-TAZ fusion proteins were efficiently translocalized into the cytosol of hMSCs. The hMSCs treated with cell-penetrating LMWP-TAZ exhibited increased expression of osteoblastic genes and protein, producing significantly higher quantities of mineralized matrix compared to free TAZ. In contrast, adipogenic differentiation of the hMSCs was blocked by treatment of LMWP-TAZ fusion protein, as reflected by reduced marker-protein expression, adipocyte fatty acid-binding protein 2, and peroxisome proliferator-activated receptor-γ messenger ribonucleic acid levels. LMWP-TAZ was applied in alginate gel for the purpose of localization and controlled release. The LMWP-TAZ fusion protein-loaded alginate gel matrix significantly increased bone formation in rabbit calvarial defects compared with alginate gel matrix mixed with free TAZ protein. The protein transduction of TAZ fused with cell-penetrating LMWP peptide was able selectively to stimulate osteogenesis in vitro and in vivo. Taken together, this fusion protein-transduction technology for osteogenic protein can thus be applied in combination with biomaterials for tissue regeneration and controlled release for tissue-engineering purposes. Keywords: protein transduction, low-molecular-weight protamine (LMWP), transcriptional coactivator with PDZ-binding motif (TAZ), selective osteogenesis, bone-tissue engineering